Animal study on factors influencing anterograde renal pelvis perfusion manometry - Liu, Xin; Li, Xing; Liao, Limin (Frontiers in Physiology, 2024)
ObjectsAnterograde renal pelvis perfusion manometry is an effective method to assist in the diagnosis of upper urinary tract obstruction.MethodsTo established a rat model of partial ureteral obstruction to explore the perfusion rate, renal pelvis volume, obstruction sites, contralateral upper urinary tract, and lower urinary tract functions, which may affect anterograde renal pelvis perfusion manometry. To measure the renal pelvis volume using ultrasound. Depending on whether clamped the contralateral ureter and it continuously emptied the bladder, perfused the renal pelvis at rate of 15, 30, 60, 90, or 120 mL/h to measure the pressure synchronously.ResultsThe research showed the renal pelvis volume of UPJ and UVJ at 1, 2, 3, and 4 weeks respectively, significantly increased compared with the control group. Comparison of the renal pelvis volume between the UPJ and UVJ groups was not statistically significant. The renal pelvis pressure of UPJ and UVJ was significantly increased compared with the control group, and the UVJ group was greater than the UPJ group. The renal pelvic pressure increased as the perfusion rate increased. Comparing the renal pelvis pressure measured using synchronous bladder emptying with the renal pelvis pressure measured singly, the difference was statistically significant. Comparing the renal pelvis pressure measured using synchronous bladder emptying with measured with a clamped contralateral ureter, the difference was not statistically significant; however, in some groups, the difference was statistically significant. Measuring the renal pelvis pressure singly and clamping the contralateral ureter, the difference was not statistically significant, except in some groups, the difference was significant.ConclusionThe study suggested that ureter obstruction sites, perfusion rates, renal pelvis volumes, and synchronous bladder emptying affects the renal pelvis pressure. The function of the contralateral upper urinary tract did not affect renal pelvis pressure in the short term.